2000
DOI: 10.1128/jvi.74.11.5233-5241.2000
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Protein 5A of Hepatitis C Virus Inhibits the Function of Karyopherin β3

Abstract: It has been suggested that nonstructural protein 5A (NS5A) of hepatitis C virus (HCV) plays a role in the incapacitation of interferon by inactivation of RNA-dependent protein kinase PKR. In order to further investigate the role of NS5A, we tried to identify cellular proteins interacting with NS5A by using the yeast two-hybrid system. The karyopherin ␤3 gene was isolated from a human liver cell library as a protein interacting with NS5A. The protein-protein interaction between NS5A and karyopherin ␤3 was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
48
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…30 Finally, NS5A might interfere with the nuclear transport of RNA and proteins by interacting with Karyopherin ␤ 3. 31 Thus, NS5A expression may play a crucial role in control of the antiviral and proliferative status of the HCV-related liver cell by interacting with several cellular signaling pathways.Abbreviations: HCV, hepatitis C virus; IFN-␣, interferon alfa; ISDR, interferon sensitivity-determining region; EMCV, encephalomyocarditis virus; VSV, vesicular stomatitis virus; PKR, double-stranded RNA-dependent kinase; PCR, polymerase chain reaction; FCS, fetal calf serum; SDS-PAGE, sodium dodecyl sulfate polyacrylamide gel electrophoresis; eIF2, eukaryotic initiation factor 2; PFU, plaque-forming unit; PBS, phosphatebuffered saline; TNF, tumor necrosis factor. From…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Finally, NS5A might interfere with the nuclear transport of RNA and proteins by interacting with Karyopherin ␤ 3. 31 Thus, NS5A expression may play a crucial role in control of the antiviral and proliferative status of the HCV-related liver cell by interacting with several cellular signaling pathways.Abbreviations: HCV, hepatitis C virus; IFN-␣, interferon alfa; ISDR, interferon sensitivity-determining region; EMCV, encephalomyocarditis virus; VSV, vesicular stomatitis virus; PKR, double-stranded RNA-dependent kinase; PCR, polymerase chain reaction; FCS, fetal calf serum; SDS-PAGE, sodium dodecyl sulfate polyacrylamide gel electrophoresis; eIF2, eukaryotic initiation factor 2; PFU, plaque-forming unit; PBS, phosphatebuffered saline; TNF, tumor necrosis factor. From…”
mentioning
confidence: 99%
“…30 Finally, NS5A might interfere with the nuclear transport of RNA and proteins by interacting with Karyopherin ␤ 3. 31 Thus, NS5A expression may play a crucial role in control of the antiviral and proliferative status of the HCV-related liver cell by interacting with several cellular signaling pathways.…”
mentioning
confidence: 99%
“…In addition, the phosphorylation pattern of NS5A plays an important role in HCV genome replication (Evans et al, 2004b;Appel et al, 2005). It also interacts with a multitude of cellular proteins and alters the host cells to support viral RNA replication (Gale et al, 1998;Chung et al, 2000;Park et al, 2002;Evans et al, 2004a;Gao et al, 2004).…”
mentioning
confidence: 99%
“…The aminoterminal domain of NS5A appears to interact with several cellular proteins (Gale et al, 1998;Chung et al, 2000;Park et al, 2002;Waris et al, 2003;Evans et al, 2004a;Gao et al, 2004) that may be necessary for replication. In addition, an amphipathic a-helix and a zinc-binding site located at the amino terminus are required for replication (Brass et al, 2002; Elazar et al, 2003;Tellinghuisen et al, 2004Tellinghuisen et al, , 2005 et al, 2000) and the carboxyterminal sequences (residues 399-441) have been demonstrated (Zhu et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation